AAA Abstract and Applied Analysis 1687-0409 1085-3375 Hindawi Publishing Corporation 584969 10.1155/2014/584969 584969 Research Article Difference Equations and Sharing Values Concerning Entire Functions and Their Difference Mao Zhiqiang 1 Liu Huifang 2 Chen Zong-Xuan 1 School of Mathematics and Computer Jiangxi Science and Technology Normal University Nanchang 330038 China jxstnu.cn 2 College of Mathematics and Information Science Jiangxi Normal University Nanchang 330022 China jxnu.edu.cn 2014 742014 2014 19 01 2014 22 03 2014 7 4 2014 2014 Copyright © 2014 Zhiqiang Mao and Huifang Liu. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

The value distribution of solutions of certain difference equations is investigated. As its applications, we investigate the difference analogue of the Brück conjecture. We obtain some results on entire functions sharing a finite value with their difference operators. Examples are provided to show that our results are the best possible.

1. Introduction and Main Results

In this paper, the term meromorphic function will mean being meromorphic in the whole complex plane . It is assumed that the reader is familiar with the standard notations and the fundamental results of the Nevanlinna theory; see, for example, . In addition, we use notations σ ( f ) , λ ( f ) to denote the order and the exponent of convergence of the sequence of zeros of a meromorphic function f , respectively. The notation S ( r , f ) is defined to be any quantity satisfying S ( r , f ) = o ( T ( r , f ) ) as r , possibly outside a set E of r of finite logarithmic measure.

Let f and g be two nonconstant meromorphic functions, and let a . We say that f and g share a CM, provided that f - a and g - a have the same zeros with the same multiplicities. Similarly, we say that f and g share a IM, provided that f - a and g - a have the same zeros ignoring multiplicities.

The famous results in the uniqueness theory of meromorphic functions are the 5 IM and 4 CM shared values theorems due to Nevanlinna . It shows that if two nonconstant meromorphic functions f and g share five different values IM or four different values CM, then f g or f is a linear fractional transformation of g . Condition 4 CM shared values have been improved to 2 CM + 2 IM by Gundersen , while the case 1 CM + 3 IM still remains an open problem. Specifically, Brück posed the following conjecture.

Conjecture 1 (see [<xref ref-type="bibr" rid="B1">6</xref>]).

Let f be a nonconstant entire function satisfying the hyperorder σ 2 ( f ) < , where σ 2 ( f ) is not a positive integer. If f and f share a finite value a CM, then f - a c ( f - a ) for some nonzero constant c .

In , Brück proved that the conjecture is true provided that a = 0 or N ( r , 1 / f ) = S ( r , f ) . He also gave counterexamples to show that the restriction on the growth of f is necessary.

In recent years, as the research on the difference analogues of Nevanlinna theory is becoming active, lots of authors  started to consider the uniqueness of meromorphic functions sharing values with their shifts or their difference operators.

Heittokangas et al. proved the following result which is a shifted analogue of Brück’s conjecture.

Theorem A (see [<xref ref-type="bibr" rid="B8">8</xref>]).

Let f be a meromorphic function of σ ( f ) < 2 and η a nonzero complex number. If f ( z ) and f ( z + η ) share a finite value a and CM, then (1) f ( z + η ) - a f ( z ) - a = τ , for some constant τ .

In , Heittokangas et al. gave the example f ( z ) = e z 2 + 1 which shows that σ ( f ) < 2 cannot be relaxed to σ ( f ) 2 .

For a nonzero complex number η , we define difference operators as (2) Δ η f ( z ) = f ( z + η ) - f ( z ) , Δ η n f ( z ) = Δ η n - 1 ( Δ η f ( z ) ) , n , n 2 . Regarding the difference analogue of Brück’s conjecture, we mention the following results.

Theorem B (see [<xref ref-type="bibr" rid="B4">7</xref>]).

Let f be a finite order transcendental entire function which has a finite Borel exceptional value a , and let η be a constant such that f ( z + η ) f ( z ) . If f ( z ) and Δ η f ( z ) share a CM, then (3) a = 0 , f ( z + η ) - f ( z ) f ( z ) = c , for some nonzero constant c .

Theorem C (see [<xref ref-type="bibr" rid="B13">11</xref>]).

Let f be a nonperiodic transcendental entire function of finite order. If f ( z ) and Δ η n f ( z ) share a nonzero finite value a CM, then 1 σ ( f ) λ ( f - a ) + 1 ; that is, (4) f ( z ) = A ( z ) e Q ( z ) + a , where A ( z ) is an entire function with σ ( A ) = λ ( f - a ) and Q ( z ) is a polynomial with deg Q σ ( A ) + 1 .

Let f be a nonperiodic transcendental entire function of finite order. Theorem B shows that if a nonzero finite value a is shared by f ( z ) and Δ η f ( z ) , then σ ( f ) = λ ( f - a ) . It is obvious that the result in Theorem B is sharper than Theorem C for n = 1 . In this paper, we continue to investigate the difference analogue of Brück’s conjecture and obtain the following result.

Theorem 2.

Let f be a finite order entire function, n 2 an integer, and η a constant such that Δ η n f ( z ) 0 . If f ( z ) and Δ η n f ( z ) share a finite value a ( 0 ) CM, then λ ( f - a ) = σ ( f ) 1 ; that is, (5) f ( z ) = A ( z ) e Q ( z ) + a , where A ( z ) is an entire function with 1 σ ( A ) = λ ( f - a ) = σ ( f ) and Q ( z ) is a polynomial with deg Q σ ( A ) .

Remark 3.

It is obvious that Theorem 2 is sharper than Theorem C and a supplement of Theorem B for n 2 .

The discussions in Theorems C and 2 are concerning the case that shared value a 0 . When a = 0 , we obtain the following result.

Theorem 4.

Let f be a finite order entire function, n a positive integer, and η a constant such that Δ η n f ( z ) 0 . If f ( z ) and Δ η n f ( z ) share 0 CM, then 1 σ ( f ) λ ( f ) + 1 ; that is, (6) f ( z ) = A ( z ) e Q ( z ) , where A ( z ) is an entire function with σ ( A ) = λ ( f ) and Q ( z ) is a polynomial with deg Q σ ( A ) + 1 .

It is well known that if a finite order entire function f ( z ) shares a CM with Δ η n f ( z ) , then f ( z ) satisfies the difference equation (7) Δ η n f ( z ) - a = e Q ( z ) ( f ( z ) - a ) , where Q ( z ) is a polynomial. Hence in order to prove the above results, we consider the value distribution of entire solutions of the difference equation (8) a n ( z ) f ( z + n η ) + + a 1 ( z ) f ( z + η ) + ( a 0 ( z ) - e Q ( z ) ) f ( z ) = B ( z ) and obtain the following result.

Theorem 5.

Let a 0 , , a n - 1 , a n ( 0 ) , B ( 0 ) be polynomials, and let Q be a polynomial with degree m ( 1 ) . Then every entire solution f of finite order of (8) satisfies σ ( f ) m and

if σ ( f ) > 1 , then λ ( f ) = σ ( f ) ;

if σ ( f ) = 1 , then λ ( f ) = σ ( f ) or f has only finitely many zeros.

2. Lemmas Lemma 6 (see [<xref ref-type="bibr" rid="B6">12</xref>]).

Let T : ( 0 , + ) ( 0 , + ) be a nondecreasing continuous function, s > 0 , α < 1 , and let F + be the set of all r such that T ( r ) α T ( r + s ) . If the logarithmic measure of F is infinite, then (9) lim ¯ r log T ( r ) log r = .

Lemma 7 (see [<xref ref-type="bibr" rid="B7">13</xref>]).

Let f be a nonconstant meromorphic function of finite order, η , δ < 1 . Then (10) m ( r , f ( z + η ) f ( z ) ) = o ( T ( r + | η | , f ) r δ ) for all r outside a possible exceptional set E with finite logarithmic measure E ( d r / r ) < .

Remark 8.

By Lemmas 6 and 7, we know that, for a nonconstant meromorphic function f of finite order, (11) m ( r , f ( z + η ) f ( z ) ) = S ( r , f ) .

Lemma 9 (see [<xref ref-type="bibr" rid="B16">3</xref>]).

Let f j ( j = 1 , , n + 1 ) and g j ( j = 1 , , n ) be entire functions such that

j = 1 n f j ( z ) e g j ( z ) f n + 1 ( z ) ,

the order of f j is less than the order of e g k for 1 j n + 1 , 1 k n ; and furthermore, the order of f j is less than the order of e g h - g k for n 2 and 1 j n + 1 , 1 h < k n .

Then f j ( z ) 0 ( j = 1 , , n + 1 ) .

Lemma 10 (see [<xref ref-type="bibr" rid="B2">14</xref>]).

Let f be a meromorphic function with finite order σ ( f ) = σ < 1 , η { 0 } . Then for any given ɛ > 0 and integers 0 j < k , there exists a set E ( 1 , ) of finite logarithmic measure, so that, for all | z | = r E [ 0,1 ] , we have (12) | Δ η k f ( z ) Δ η j f ( z ) | | z | ( k - j ) ( σ - 1 ) + ɛ .

Lemma 11 (see [<xref ref-type="bibr" rid="B3">15</xref>]).

Let a 0 ( z ) , , a k ( z ) be entire functions with finite order. If there exists an integer l ( 0 l k ) such that (13) σ ( a l ) > max 0 j k j l { σ ( a j ) } holds, then every meromorphic solution f ( 0 ) of the difference equation (14) a k ( z ) f ( z + k ) + + a 1 ( z ) f ( z + 1 ) + a 0 ( z ) f ( z ) = 0 satisfies σ ( f ) σ ( a l ) + 1 .

3. Proofs of Results Proof of Theorem <xref ref-type="statement" rid="thm1.3">5</xref>.

Let f be an entire solution of finite order of (8). By Remark 8 and (8), we get (15) T ( r , e Q ) = T ( r , e Q - a 0 ) + S ( r , e Q ) j = 1 n m ( r , f ( z + j η ) f ( z ) ) + j = 0 n m ( r , a j ) + m ( r , B ( z ) f ( z ) ) + S ( r , e Q ) T ( r , f ) + S ( r , f ) + S ( r , e Q ) . By (15) we get σ ( f ) m .

Case  1 ( σ ( f ) > 1 ). Suppose that λ ( f ) < σ ( f ) , by the Weierstrass factorization; we get f ( z ) = h 1 ( z ) e h 2 ( z ) , where h 1 ( z ) ( 0 ) is an entire function and h 2 ( z ) is a polynomial such that (16) σ ( h 1 ) = λ ( h 1 ) = λ ( f ) < σ ( f ) = deg h 2 . Substituting f ( z ) = h 1 ( z ) e h 2 ( z ) into (8), we get (17) j = 1 n a j ( z ) h 1 ( z + j η ) e h 2 ( z + j η ) - h 2 ( z ) + ( a 0 ( z ) - e Q ( z ) ) h 1 ( z ) = B ( z ) e - h 2 ( z ) . If deg h 2 > m , then by (16) we know that the order of the right side of (17) is deg h 2 , and the order of the left side of (17) is less than deg h 2 . This is a contradiction. Hence deg h 2 = m > 1 . Set (18) Q ( z ) = b m z m + + b 0 , h 2 ( z ) = c m z m + + c 0 , where b m ( 0 ) , , b 0 , c m ( 0 ) , , c 0 are complex numbers. By (17) we get (19) j = 1 n a j ( z ) h 1 ( z + j η ) e h 2 ( z + j η ) - h 2 ( z ) + a 0 ( z ) h 1 ( z ) = h 1 ( z ) e Q ( z ) + B ( z ) e - h 2 ( z ) . Next we discuss the following two subcases.

Subcase 1 ( b m + c m 0 ). Then by Lemma 9, (16), and (19), we get B ( z ) 0 , h 1 ( z ) 0 . This is impossible.

Subcase  2 ( b m + c m = 0 ). Suppose that (20) h 1 ( z ) e Q ( z ) - b m z m + B ( z ) e - h 2 ( z ) - b m z m 0 . Then h 1 ( z ) = - B ( z ) e - h 2 ( z ) - Q ( z ) . By σ ( h 1 ) = λ ( h 1 ) , we obtain that e - h 2 ( z ) - Q ( z ) is a nonzero constant. Hence h 1 ( z ) is a nonzero polynomial. By (19) we get (21) j = 1 n a j ( z ) h 1 ( z + j η ) e h 2 ( z + j η ) - h 2 ( z ) = - a 0 ( z ) h 1 ( z ) . Since deg { h 2 ( z + j η ) - h 2 ( z + i η ) } = m - 1 > 0 for i j , then by Lemma 9 and (21), we get (22) a j ( z ) h 1 ( z + j η ) 0 ( j = 0,1 , , n ) . This is impossible. Hence we have h 1 ( z ) e Q ( z ) - b m z m + B ( z ) e - h 2 ( z ) - b m z m 0 . Then from the order consideration, we know that the order of the right side of (19) is m , and the order of the left side of (19) is less than m . This is a contradiction. Hence λ ( f ) = σ ( f ) .

Case  2 ( σ ( f ) = 1 ). Then by σ ( f ) m , we get m = 1 . Suppose that f ( z ) has infinitely many zeros and λ ( f ) < σ ( f ) ; by the Weierstrass factorization, we get (23) f ( z ) = h 3 ( z ) e β z , where β ( 0 ) is a complex number and h 3 ( z ) ( 0 ) is an entire function such that (24) σ ( h 3 ) = λ ( h 3 ) = λ ( f ) < 1 . Let Q ( z ) = b 1 z + b 0 , where b 1 ( 0 ) , b 0 are complex numbers. Substituting f ( z ) = h 3 ( z ) e β z into (8), we get (25) j = 1 n a j ( z ) h 3 ( z + j η ) e β j η + a 0 ( z ) h 3 ( z ) = h 3 ( z ) e b 1 z + b 0 + B ( z ) e - β z . Note that h 3 ( z ) e b 0 + B ( z ) 0 ; otherwise f has only finitely many zeros. If b 1 + β = 0 , then the order of the right side of (25) is 1, but the order of the left side of (25) is less than 1. This is absurd. If b 1 + β 0 , then by Lemma 9, (24), and (25), we get h 3 ( z ) 0 , B ( z ) 0 . This is impossible. Hence λ ( f ) = σ ( f ) . Theorem 5 is thus completely proved.

Proof  of Theorem <xref ref-type="statement" rid="thm1.1">2</xref>.

Since f ( z ) and Δ η n f ( z ) share a CM and f is of finite order, then (26) Δ η n f ( z ) - a f ( z ) - a = e Q ( z ) , where Q ( z ) is a polynomial with deg Q σ ( f ) . Now we will take two steps to complete the proof.

Step  1. We prove that λ ( f - a ) = σ ( f ) .

Let F ( z ) = f ( z ) - a ; then (27) λ ( F ) = λ ( f - a ) , σ ( F ) = σ ( f ) deg Q , and Δ η n f ( z ) = Δ η n F ( z ) = j = 0 n ( n j ) ( - 1 ) n - j F ( z + j η ) . By this and (26), we get (28) j = 1 n ( n j ) ( - 1 ) n - j F ( z + j η ) + ( ( - 1 ) n - e Q ( z ) ) F ( z ) = a . Next we discuss the following three cases.

Case 1 ( deg Q 1   and   σ ( F ) > deg Q ). Then σ ( F ) > 1 . By Theorem 5(i), (27), and (28), we get λ ( f - a ) = σ ( f ) .

Case 2 ( deg Q 1 and   σ ( F ) = deg Q ). If σ ( F ) = deg Q > 1 , then by Theorem 5(i), (27), and (28), we get λ ( f - a ) = σ ( f ) . If σ ( F ) = deg Q = 1 , then by Theorem 5(ii) and (27), we obtain that λ ( f - a ) = σ ( f ) , or F has only finitely many zeros.

If F has only finitely many zeros, set (29) F ( z ) = h 1 ( z ) e b z , where h 1 ( z ) ( 0 ) is a polynomial and b ( 0 ) is a complex number; then substituting (29) into (28), we get (30) j = 1 n ( n j ) ( - 1 ) n - j h 1 ( z + j η ) e b j η + ( - 1 ) n h 1 ( z ) = h 1 ( z ) e Q ( z ) + a e - b z . By (30) and Δ η n F ( z ) 0 , we know that the order of the left side of (30) is 0 and the order of the right side of (30) is 1 unless h 1 ( z ) = - a and Q ( z ) = - b z . In this case, take it into the left side of (30); we have ( - a ) ( e b η - 1 ) n = 0 . Since all a , b , and η are not zero, it is impossible. Hence we get λ ( f - a ) = σ ( f ) .

Case  3. Q is a complex constant. Then by (28) we get (31) j = 1 n ( n j ) ( - 1 ) n - j F ( z + j η ) + ( ( - 1 ) n - c ) F ( z ) = a , where c ( = e Q 0 ) is a complex number. Suppose that λ ( F ) < σ ( F ) . Let F ( z ) = h 2 ( z ) e h 3 ( z ) , where h 2 ( z ) ( 0 ) is an entire function and h 3 ( z ) is a polynomial such that (32) σ ( h 2 ) = λ ( h 2 ) = λ ( F ) < σ ( F ) = deg h 3 . Substituting F ( z ) = h 2 ( z ) e h 3 ( z ) into (31), we get (33) j = 1 n ( n j ) ( - 1 ) n - j h 2 ( z + j η ) e h 3 ( z + j η ) - h 3 ( z ) + ( ( - 1 ) n - c ) h 2 ( z ) = a e - h 3 ( z ) . Since deg ( h 3 ( z + j η ) - h 3 ( z ) ) = deg h 3 ( z ) - 1 , ( j = 1 , , n ) , by (32) we obtain that the order of the left side of (33) is less than deg h 3 and the order of the right side of (33) is deg h 3 . This is absurd. Hence we get λ ( f - a ) = σ ( f ) .

Step  2. We prove that σ ( f ) 1 .

Suppose that σ ( f ) < 1 . Since f ( z ) and Δ η n f ( z ) share a CM, then (34) Δ η n f ( z ) - a f ( z ) - a = c , where c is a nonzero constant. Let F ( z ) = f ( z ) - a ; then by (34) we get (35) Δ η n F ( z ) = c F ( z ) + a . Differentiating (35), we get (36) ( Δ η n F ( z ) ) = c F ( z ) . Note that ( Δ η n F ( z ) ) = Δ η n ( F ( z ) ) and σ ( F ) = σ ( F ) = σ ( f ) < 1 . So by Lemma 10 and (36), we get (37) | c | = | Δ η n ( F ( z ) ) F ( z ) | | z | n ( σ ( F ) - 1 ) + ɛ 0 . This is absurd. So σ ( f ) 1 . Theorem 2 is thus completely proved.

Proof of Theorem <xref ref-type="statement" rid="thm1.2">4</xref>.

Since f ( z ) and Δ η n f ( z ) share 0 CM and f is of finite order, then (38) Δ η n f ( z ) f ( z ) = e Q ( z ) , where Q ( z ) is a polynomial. By Δ η n f = j = 0 n ( n j ) ( - 1 ) n - j f ( z + j η ) and (38), we get (39) f ( z + n η ) + j = 1 n - 1 ( n j ) ( - 1 ) n - j f ( z + j η ) + ( ( - 1 ) n - e Q ( z ) ) f ( z ) = 0 . We discuss the following two cases.

Case  1. Q is a polynomial with deg Q = m 1 . Then by Lemma 11 and (39), we get σ ( f ) m + 1 . Now we prove σ ( f ) λ ( f ) + 1 . Suppose that σ ( f ) > λ ( f ) + 1 ; then by the Weierstrass factorization, we get f ( z ) = h 1 ( z ) e h 2 ( z ) , where h 1 ( z ) ( 0 ) is an entire function and h 2 ( z ) is a polynomial such that (40) σ ( h 1 ) = λ ( h 1 ) = λ ( f ) , σ ( f ) = deg h 2 > σ ( h 1 ) + 1 . Substituting f ( z ) = h 1 ( z ) e h 2 ( z ) into (39), we get (41) j = 1 n ( n j ) ( - 1 ) n - j h 1 ( z + j η ) e h 2 ( z + j η ) - h 2 ( z ) + ( - 1 ) n h 1 ( z ) = h 1 ( z ) e Q ( z ) .

If σ ( f ) > m + 1 , then by (40), (41), and deg ( h 2 ( z + j η ) - h 2 ( z ) ) = deg h 2 ( z ) - 1 , ( j = 1 , , n ) , we obtain that the order of the left side of (41) is deg h 2 - 1 and the order of the right side of (41) is less than deg h 2 - 1 . This is absurd.

If σ ( f ) = m + 1 , then by (41) we get (42) j = 1 n ( n j ) ( - 1 ) n - j h 1 ( z + j η ) e h 2 ( z + j η ) - h 2 ( z ) - h 1 ( z ) e Q ( z ) = ( - 1 ) n + 1 h 1 ( z ) . Set (43) h 2 ( z ) = d m + 1 z m + 1 + + d 0 , where d m + 1 ( 0 ) , , d 0 are complex numbers. Then (44) h 2 ( z + j η ) - h 2 ( z ) = d m + 1 ( m + 1 ) j η z m + + d 1 j η , h h h h h h h h h h h h h h h h h ( j = 1 , , n ) . Now we discuss the following two subcases.

Subcase  1. deg ( Q ( z ) - ( h 2 ( z + j η ) - h 2 ( z ) ) ) = m holds for every j { 1 , , n } . Then by (40), (42), deg ( h 2 ( z + j η ) - h 2 ( z + i η ) ) = m , ( j i ) , and Lemma 9, we get h 1 ( z ) 0 . This is absurd.

Subcase  2. There exist some j 0 { 1 , , n } such that deg ( Q ( z ) - ( h 2 ( z + j 0 η ) - h 2 ( z ) ) ) m - 1 . Then by (44) we have deg ( Q ( z ) - ( h 2 ( z + j η ) - h 2 ( z ) ) ) = m for j j 0 . Merging the term - h 1 ( z ) e Q ( z ) into ( n j 0 ) ( - 1 ) n - j 0 h 1 ( z + j 0 η ) e h 2 ( z + j 0 η ) - h 2 ( z ) , by (42) we get (45) j = 1 j j 0 n ( n j ) ( - 1 ) n - j h 1 ( z + j η ) e h 2 ( z + j η ) - h 2 ( z ) + A ( z ) e h 2 ( z + j 0 η ) - h 2 ( z ) hh = ( - 1 ) n + 1 h 1 ( z ) , ( n 2 ) , or (46) A ( z ) e h 2 ( z + j 0 η ) - h 2 ( z ) = ( - 1 ) n + 1 h 1 ( z ) , ( n = 1 ) , where A ( z ) = ( n j 0 ) ( - 1 ) n - j 0 h 1 ( z + j 0 η ) - h 1 ( z ) e Q ( z ) - ( h 2 ( z + j 0 η ) - h 2 ( z ) ) satisfying σ ( A ) < m . If n 2 , then by (40), (45), deg ( h 2 ( z + j η ) - h 2 ( z + i η ) ) = m , ( j i ) , and Lemma 9, we get h 1 ( z ) 0 . This is absurd. If n = 1 , then by (46) and h 1 ( z ) 0 , we get A ( z ) 0 . By this we know that the order of the left side of (46) is m and the order of the right side of (46) is less than m . This is absurd. Hence we get σ ( f ) λ ( f ) + 1 .

Case  2. Q is a complex constant. Then by Lemma 10 and (38), we get σ ( f ) 1 . Now we prove σ ( f ) λ ( f ) + 1 . Suppose that σ ( f ) > λ ( f ) + 1 . If σ ( f ) > 1 , then by the similar argument to that of case 1, we get h 1 ( z ) 0 . This is absurd. If σ ( f ) = 1 , then by (40) we get 0 λ ( f ) < σ ( f ) - 1 = 0 . Since λ ( f ) = 0 , then σ ( f ) = λ ( f ) + 1 . Theorem 4 is thus completely proved.

4. Some Examples

The following examples show the existence of such entire functions which satisfy Theorems 25. Moreover, Example 2 shows that the result in Theorem 4 is the best possible.

Example 1.

Let η = 1 , n = 2 , and f ( z ) = ( d + 1 ) z + ( ( d 2 - 1 ) / d 2 ) a , where a ( 0 ) , d ( 0 , ± 1 ) are constants. Then f ( z ) and Δ η n f ( z ) share a CM and σ ( f ) = λ ( f - a ) = 1 .

Example 2.

Let η = 1 , n = 2 , and f ( z ) = e z . Then f ( z ) and Δ η n f ( z ) share 0 CM and σ ( f ) = 1 = λ ( f ) + 1 .

Example 3.

Let η = 1 , n = 2 , and f ( z ) = H ( z ) e z , where H ( z ) is an entire function with period 1 such that σ ( H ) > 1 and σ ( H ) . Then f ( z ) and Δ η n f ( z ) share 0 CM and λ ( f ) = λ ( H ) = σ ( H ) = σ ( f ) > 1 . (Ozawa  proved that for any σ [ 1 , ) there exists a period entire function of order σ .)

Example 4.

The entire function f ( z ) = z e - z satisfies the difference equation (47) f ( z + 2 η ) - 4 f ( z + η ) + ( 4 - e z ) f ( z ) = - z , where η = - log 2 . Here σ ( f ) = 1 and f has only finitely many zeros.

Conflict of Interests

The authors declare that there is no conflict of interests regarding the publication of this paper.

Acknowledgments

This work is supported by the National Natural Science Foundation of China (nos. 11201195, 11171119) and the Natural Science Foundation of Jiangxi, China (nos. 20122BAB201012, 20132BAB201008.).

Hayman W. K. Meromorphic Functions 1964 Oxford, UK Clarendon Press MR0164038 Laine I. Nevanlinna Theory and Complex Differential Equations 1993 Berlin, Germany Walter de Gruyter 10.1515/9783110863147 MR1207139 Yang C.-C. Yi H.-X. Uniqueness Theory of Meromorphic Functions 2003 New York, NY, USA Kluwer Academic Publishers MR2105668 Nevanlinna R. Le Theoreme de Picard-Borel et la Theorie des Fonctions Meromorphes 1929 Paris, France Gauthiers-Villars Gundersen G. G. Meromorphic functions that share four values Transactions of the American Mathematical Society 1983 277 2 545 567 10.2307/1999223 MR694375 ZBL0508.30029 Brück R. On entire functions which share one value CM with their first derivative Results in Mathematics 1996 30 1-2 21 24 10.1007/BF03322176 MR1402421 ZBL0861.30032 Chen Z.-X. Yi H.-X. On sharing values of meromorphic functions and their differences Results in Mathematics 2013 63 1-2 557 565 10.1007/s00025-011-0217-7 MR3009705 ZBL1267.30077 Heittokangas J. Korhonen R. Laine I. Rieppo J. Zhang J. Value sharing results for shifts of meromorphic functions, and sufficient conditions for periodicity Journal of Mathematical Analysis and Applications 2009 355 1 352 363 10.1016/j.jmaa.2009.01.053 MR2514472 ZBL1180.30039 Heittokangas J. Korhonen R. Laine I. Rieppo J. Uniqueness of meromorphic functions sharing values with their shifts Complex Variables and Elliptic Equations 2011 56 81 92 10.1080/17476930903394770 MR2774582 ZBL1217.30029 Liu K. Yang L.-Z. Value distribution of the difference operator Archiv der Mathematik 2009 92 3 270 278 10.1007/s00013-009-2895-x MR2496679 ZBL1173.30018 Li S. Gao Z. A note on the Brück conjecture Archiv der Mathematik 2010 95 3 257 268 10.1007/s00013-010-0165-6 MR2719384 ZBL1213.30058 Halburd R. G. Korhonen R. J. Nevanlinna theory for the difference operator Annales Academiæ Scientiarum Fennicæ. Mathematica 2006 31 2 463 478 MR2248826 ZBL1108.30022 Halburd R. G. Korhonen R. J. Difference analogue of the lemma on the logarithmic derivative with applications to difference equations Journal of Mathematical Analysis and Applications 2006 314 2 477 487 10.1016/j.jmaa.2005.04.010 MR2185244 ZBL1085.30026 Chiang Y.-M. Feng S.-J. On the growth of logarithmic differences, difference quotients and logarithmic derivatives of meromorphic functions Transactions of the American Mathematical Society 2009 361 7 3767 3791 10.1090/S0002-9947-09-04663-7 MR2491899 ZBL1172.30009 Chiang Y.-M. Feng S.-J. On the Nevanlinna characteristic of f ( z + η ) and difference equations in the complex plane Ramanujan Journal 2008 16 1 105 129 10.1007/s11139-007-9101-1 MR2407244 ZBL1152.30024 Ozawa M. On the existence of prime periodic entire functions Kōdai Mathematical Seminar Reports 1978 29 3 308 321 MR510300